2000
DOI: 10.1139/f00-125
|View full text |Cite
|
Sign up to set email alerts
|

Comparative impacts of fire and forest harvesting on water quality in Boreal Shield lakes

Abstract: Water quality was monitored in Boreal Shield lakes for 3 years following their simultaneous impact by clearcut logging or wildfire. Seventeen similar undisturbed lakes served as references. Dissolved organic carbon (DOC) and the light attenuation coefficient (εPAR) were up to threefold higher in cut lakes than in reference and burnt lakes. Compared with median values for reference lakes, cut and burnt lakes had higher concentrations of total phosphorus (TP) (two- to three-fold), total organic nitrogen (TON) (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(181 citation statements)
references
References 21 publications
10
167
2
2
Order By: Relevance
“…Moreover, it has been shown that in reservoirs the recycling of allochthonous organic matter enhances aquatic productivity and that the main pathway of carbon flow to secondary producers shifted from an autochthonous to an allochthonous base originating from flooded vegetation (Paterson et al 1997). In some natural lakes, the substantial increase in runoff of soil nutrients resulting from large-scale perturbations to their watershed (deforestation, Carignan et al 2000;wetland drainage, Hambright et al 2004) has also been invoked to explain enhanced levels of primary productivity and concomitant transfer of algal carbon to sediments (Meyers 2003). The study at the Experimental Lake Area in northwestern Ontario (Paterson et al 1997) revealed that the response of in situ productivity and food web structure to reservoir flooding is rapid and results from pulse inputs of phosphorus, nitrogen, and dissolved carbon to the water column (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that in reservoirs the recycling of allochthonous organic matter enhances aquatic productivity and that the main pathway of carbon flow to secondary producers shifted from an autochthonous to an allochthonous base originating from flooded vegetation (Paterson et al 1997). In some natural lakes, the substantial increase in runoff of soil nutrients resulting from large-scale perturbations to their watershed (deforestation, Carignan et al 2000;wetland drainage, Hambright et al 2004) has also been invoked to explain enhanced levels of primary productivity and concomitant transfer of algal carbon to sediments (Meyers 2003). The study at the Experimental Lake Area in northwestern Ontario (Paterson et al 1997) revealed that the response of in situ productivity and food web structure to reservoir flooding is rapid and results from pulse inputs of phosphorus, nitrogen, and dissolved carbon to the water column (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable debate in Canada as to whether management techniques must emulate these natural disturbances to sustain forest dynamics and biodiversity (Hunter, 1993). Hydrochemical responses to natural disturbances such as fire have (Schindler et al, 1980;Bayley et al, 1992;Carignan et al, 2000) and continue to be a major research focus. For example, Prepas et al (2003) found greater water yield during stormflow periods and increased particulate P export from a burned relative to a forested reference basin in central Alberta.…”
Section: Disturbed Conditionsmentioning
confidence: 99%
“…Whether there will be an increased export of N after harvesting to aquatic systems depends on the coincident occurrence of increased production and/or decreased uptake by plants and microorganisms within the terrestrial ecosystem and the ability to transfer these nutrients to adjacent receiving waters. The minimal surface water impacts of harvesting reported for the Canadian boreal forest region (Nicolson et al, 1982;Carignan et al, 2000;Lamontagne et al, 2000;Steedman 2000;Prepas et al, 2001), even in studies where no shoreline buffer zones had been established, may be partly explained by the limited potential of upland boreal forest soils to mineralize organic-N to inorganic forms. In general, unharvested boreal forest organic and mineral soils have been shown to have low net inorganic-N production, particularly NO À 3 -N. This has been shown in Quebec (Brais et al, 1995;Smith et al, 2000) and Michigan (Stottlemyer and Toczydlowski, 1999) on the boreal shield and in Saskatchewan on the boreal plain (Walley et al, 1996).…”
Section: Introductionmentioning
confidence: 99%